Pengaruh penggunaan buku siswa IPA terpadu model shared dengan tema kohesi dan adhesi pada lingkungan terhadap hasil belajar peserta didik kelas VII SMPN 4 Padang - Nessa Aqila; Ratnawulan Ratnawulan; Gusnedi Gusnedi (Universitas Negeri Padang, 2019)
Based on the 2013 curriculum the implementation of science learning in junior high school was developed as an integrated science or integrated science subject. This concept of cohesiveness is demonstrated by integrating science concepts from the fields of physics, chemistry and biology. In fact in the school the implementation of science learning is still taught separately and the lack of understanding of students regarding the integration of science material. The solution to this problem is to implement a Shared Model Integrated IPA Student Book with Cohesion and Adhesion Themes in the Environment. This study aims to investigate the effect of integrated science student books on a shared model with the theme of cohesion and adhesion to the environment towards the learning outcomes of VII grade students of SMP 4 Padang. The type of research is Quasi Experiment Research and the research design is Randomized Control Group Only Design. All class VII students of SMP 4 Padang who were enrolled in the 2018/2019 school year were the study population. Sampling in the study was carried out by purposive sampling technique. The sample in this study consisted of two classes namely the experimental class and the control class. The research instrument consisted of learning outcome test sheets to assess aspects of knowledge and performance assessment sheets for aspects of student skills. Data in this study were analyzed by using two similarity test analysis on average, simple linear regression test, and product moment correlation analysis. The results of data analysis show that the average value of the experimental class is higher than the control class in the competency of knowledge and skills. The results of the regression analysis indicate that there is a low relationship between the use of integrated science student books shared models with the theme of cohesion and adhesion to the environment towards student learning outcomes in aspects of knowledge and skills. The contribution of the use of integrated science student books in the shared model with the theme of cohesion and adhesion to the environment towards the improvement of knowledge competency learning outcomes was 5,9% while the increase in skills competency learning outcomes was 8,41%. The results of the broad-scale effectiveness test for aspects of classical completeness knowledge of 55.55% are categorized as ineffective, while for the aspects of classical completeness skills of 100% are categorized as effective by category A.